2008
DOI: 10.1111/j.1365-2141.2008.07298.x
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnostic and prognostic significance of a specific Th1/Th2 cytokine pattern in children with haemophagocytic syndrome

Abstract: Summary The haemophagocytic syndrome (HPS) is a rare but frequently fatal disorder of immune regulation caused by hypercytokinemia. Using cytometric bead array technique, the serum T‐helper cell type 1 (Th1) and 2 (Th2) cytokines including interferon‐γ (IFN‐γ), tumour necrosis factor (TNF), interleukin (IL)‐10, IL‐6, IL‐4 and IL‐2 were determined in 24 children with de novo HPS and 87 children as control. The median levels of serum IFN‐γ, IL‐10 and IL‐6 in the acute phase of HPS were 901·7, 879·0 and 63·8 pg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
115
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(130 citation statements)
references
References 33 publications
12
115
1
Order By: Relevance
“…A cytokine panel obtained 4 days after blinatumomab and 1 day prior to tocilizumab included elevated IL-10 (5338 pg/mL), IL-6 (681 pg/mL), INF-g (192 pg/mL), and IL-2R (4872 pg/mL), helping to confirm the diagnosis of HLH/MAS (Figure 2). 7,8,14,15 After tocilizumab, his cytokines dramatically improved. PRF1, STX1, STXBP2, and MUNC13-4 mutation testing was normal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cytokine panel obtained 4 days after blinatumomab and 1 day prior to tocilizumab included elevated IL-10 (5338 pg/mL), IL-6 (681 pg/mL), INF-g (192 pg/mL), and IL-2R (4872 pg/mL), helping to confirm the diagnosis of HLH/MAS (Figure 2). 7,8,14,15 After tocilizumab, his cytokines dramatically improved. PRF1, STX1, STXBP2, and MUNC13-4 mutation testing was normal.…”
Section: Methodsmentioning
confidence: 99%
“…6 These 3 cytokines are also markedly elevated in children with hemophagocytic lymphohistiocytosis (HLH), also known as macrophage activation syndrome (MAS). 7,8 Several patients receiving CD19-specific chimeric antigen receptor-modified T cells (CART-19) have developed cytokine release syndrome (CRS), also marked by elevated IL-6, IL-10, and INF-g. 9 CART-19 is effective in chronic lymphocytic leukemia 10 and is being studied in pediatric B-ALL (NCT01626495). Our group observed that children with B-ALL receiving CART-19 develop CRS with clinical HLH/MAS.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic inflammatory processes (such as sepsis) do not tend to display the specific constellation of immunopathologies and/or evidence of T-cell activation, as seen in HLH. 14 Furthermore, whereas rising neutrophil counts, platelet counts, and ‡Although the HLH-2004 protocol uses ferritin Ͼ 500 ng/mL, we generally view ferritin Ͼ 3000 ng/mL as concerning for HLH and ferritin Ͼ 10 000 as highly suspicious. 8 §Elevations above age-adjusted, laboratory-specific normal levels (defined as Ͼ 2 SD from the mean) appear more meaningful than the original designation of Ͼ 2400 U/mL because of variations between laboratories.…”
Section: Understanding the Patterns Of Hlhmentioning
confidence: 99%
“…Measuring cytokine alterations during HIV infection [11][12][13][14][15][16] and other pathological states [17][18][19][20][21] is increasingly being investigated for use in predicting disease progression.…”
Section: Introductionmentioning
confidence: 99%